Romantic morality in Mariano Iberico and William James - Orozco, Richard Antonio (2013)
In this paper, the author offers an analysis of the evolution in Mariano Iberico’s moral philosophy that would have happened between two of his publications in the decade of the twenties. In the first publication, Iberico defends a morality of a dualistic type, giving birth to an ideal on the basis of overcoming the existential self along with its interests, needs and urgencies. A metaphysical type of morality would have been the result of such a claim. Six years later, on the other hand, the author presents a morality more understanding of the human contradiction, which does not demand the overcoming of the self as moral ideal, but rather recognizes the value of the individual. The hypothesis of this work suggests that the above mentioned evolution in Iberico’s thought would have originated from the reading of William James and of other authors whom Iberico named ‘romantics’. Furthermore, in a later section, the author shows that such an interpretationof James’ morality comes much closer to the interpretations made by Ralph B.Perry and recently by Ramon del Castillo.